(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Agricultural digitalization offers new opportunities across the world, and holds promises for enhanced productivity growth and improved well-being of all citizens. However, a significant gender gap in the access, use and ownership of digital technologies is still present in many economies and beyond, limiting the equitable realization of the benefits of digital transformation. Gender access to digital tools and digital competencies affect rural smallholders’ participation in agricultural digitalization. Total harmonization of both men and women in agricultural digitalization is a road map to agricultural sustainability and food security. Placing gender divide gaps among farmers in terms of access to technological tools will not only create a lacuna in the field of agriculture but also will subject the people to hunger and starvation. Gender-inclusive solutions that help address barriers related to access, knowledge and skills, among others, are highlighted in this paper. Closing the gender gap in agriculture would produce significant gains for society by increasing agricultural productivity, reducing poverty and hunger, and increasing economic growth of the nation. Gender participation in agricultural digitalization is hampered by structural challenges, such as access to internet connectivity, poor or weak infrastructure, policy environment and regulations, and the limited ability of individuals to use the digital solutions. Despite all these challenges, women generally have great potentials for sustaining agricultural production and family income, if given adequate incentives and gender equity. Improvement in their social status and productivity is to increase output. Therefore, women should be allowed to have access to all the productive resources necessary for agricultural production. This paper looks at digitalization in agriculture from gender perspective. It investigates the prospects and challenges of gender participation in agricultural digitalization and zooms in on the potential opportunities that digitalization provides to women, especially in the developing world, and on the obstacle they face to benefit from it.